2016
DOI: 10.1007/s10753-016-0483-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NLRP3 Inflammasome Prevents LPS-Induced Inflammatory Hyperalgesia in Mice: Contribution of NF-κB, Caspase-1/11, ASC, NOX, and NOS Isoforms

Abstract: The nucleotide-binding domain and leucine-rich repeat protein 3 (NLRP3), an intracellular signaling molecule that senses many environmental- and pathogen/host-derived factors, has been implicated in the pathogenesis of several diseases associated with inflammation. It has been suggested that NLRP3 inflammasome inhibitors may have a therapeutic potential in the treatment of NLRP3-related inflammatory diseases. The aim of this study was to determine whether inhibition of NLRP3 inflammasome prevents inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 71 publications
3
31
0
1
Order By: Relevance
“…TLR4/NF‐κB signaling pathway was reported to be involved in the pathogenesis of AD, and the NF‐κB signaling cascade was a necessary prerequisite for the activation of both canonical and noncanonical inflammasome according to previous research . We then examined whether EGCG treatment regulated TLR4/NF‐κB pathway in LPS+Aβ‐induced BV2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…TLR4/NF‐κB signaling pathway was reported to be involved in the pathogenesis of AD, and the NF‐κB signaling cascade was a necessary prerequisite for the activation of both canonical and noncanonical inflammasome according to previous research . We then examined whether EGCG treatment regulated TLR4/NF‐κB pathway in LPS+Aβ‐induced BV2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Dolunay et al showed that the inhibition of NLRP3/ASC/pro-caspase-1 inflammasome formation and activity prevents LPS-induced inflammatory hyperalgesia in mice. 54,55 However, whether IL-1β activates the NLRP3 inflammasome has seldom been studied. In this study, we showed for the first time that in NP cells, IL-1β treatment activated the NLRP3 inflammasome in time-and dose-dependent manners.…”
Section: Discussionmentioning
confidence: 99%
“…MCC950 blocks ASC oligomerization and the activation of caspase-1 and IL-1β in mouse and human macrophages. 135 Thus, MCC950 reduces IL-1β production and may serve as a potential target for inflammatory diseases [136][137][138] It also provides protection against injury. MCC950 significantly reduces the development of atherosclerotic lesions, cardiac infarction and brain injury after intracerebral haemorrhage in mice.…”
Section: Inflammasome Inhibitorsmentioning
confidence: 99%